Pengaruh Motivasi dan Kepuasan Kerja terhadap Organizational Citizenship Behavior Islam - nur ahmad budi yulianto (JIOSE: Journal of Indonesian Sharia Economics, 2022)
One of the very complex HR problems is the provision of motivation according to the needs of each employee so that ultimately employees feel satisfied in working in a company, both material and non-material motivation and job satisfaction. This study aims to determine the effect of motivation and job satisfaction on Islamic organizational citizenship behavior (OCB). This research is quantitative research based on explanatory research using sampling the saturated sample method by distributing questionnaires to the furniture industry employees of Budi Jaya Jepara. The analysis method uses Partial Least Square (PLS) with the help of WARP-PLS 0.3 software. The results of this study indicate that motivation affects job satisfaction. Job satisfaction affects Islamic organizational citizenship behavior (OCB) and motivation does not directly affect Islamic organizational citizenship behavior (OCB) because of differences in the salary system and marital status.